Bi-based amorphous glass, CBS microcrystalline glass and alumina ceramic composite low-temperature co-fired ceramic material as well as preparation method and application thereof
By using Bi2O3-ZnO-Al2O3-B2O3 and CaO-B2O3-SiO2 as glass phases in low-temperature co-fired ceramic (LTCC) materials, and combining alumina as ceramic phases, the glass ratio of glass/ceramic composites is adjusted, and the problem of insufficient research on the CaO-SiO2-B2O3 system in the prior art is solved, and LTCC materials with high thermal conductivity, high bending resistance and excellent dielectric properties are achieved.
Patent Information
- Application Number
- CN202411934583.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, the research on the CaO-SiO2-B2O3 (CBS) system of microcrystalline glass is insufficient, resulting in insufficient excellent performance in low-temperature co-fired ceramic (LTCC) materials.
Bi2O3-ZnO-Al2O3-B2O3 (BZAB) and CaO-B2O3-SiO2 (CBS) are used as the glass phase and alumina (Al2O3) is combined as the ceramic phase. By adjusting the glass ratio in the glass/ceramic composite, the sintering situation, dielectric properties and mechanical properties are improved.
The prepared high thermal conductivity, high bending Bi-based amorphous glass + CBS microcrystalline glass/alumina ceramic composite LTCC material is sintered and densely below 900°C, with a dielectric constant of 9.18-7.21, a dielectric loss of 0.9×10-3-1.6×10-3 (1MHz), a bending strength of 300±41MPa, and a thermal conductivity of 4.25W/m·K.
Smart Images

Figure CN119707459A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic materials, and in particular to a high thermal conductivity, high bending resistance glass / alumina ceramic composite low temperature co-fired ceramic (LTCC) material, a preparation method and applications thereof. Background Art
[0002] With the rapid evolution of mobile communication technology, humanity has entered the fifth generation of mobile communications, also known as the 5G era. Communication frequencies have expanded from low-frequency microwaves to high-frequency millimeter waves and terahertz, effectively alleviating the shortage of frequency band resources. With the increase in communication frequencies, low-temperature co-fired ceramics (LTCC) microwave dielectric ceramics have become a research focus. LTCC microwave dielectric ceramics refer to ceramic materials that can be co-fired with Ag electrodes at temperatures below 900°C. They primarily include three categories: glass-ceramic LTCC ceramics, glass / ceramic composite LTCC ceramics, and single-phase LTCC ceramics.
[0003] Glass / ceramic composite LTCC ceramics are made of glass and ceramic powders. Through mixing, molding, and sintering, glass / ceramic (glass + ceramic) two-phase composite LTCC materials are obtained. By adjusting the ratio of the ceramic phase to the glass phase and the properties of the precipitated crystalline phase, the directional design of the material can be achieved. The process is simple and flexible, the performance is stable, and it has great commercial application value.
[0004] Most commercial LTCC material systems are a combination of Al2O3 (aluminum oxide) and low-loss glass. Aluminum oxide is considered a workhorse in the microelectronics industry due to its low dielectric constant, low loss, high thermal conductivity, and low cost. Bismuth-based glass has gained widespread attention due to its high dielectric constant, high density, high thermal conductivity, and high polarizability. The CaO-SiO2-B2O3 (CBS) glass-ceramic LTCC system, with its low sintering temperature and excellent microwave performance, has also been extensively studied in recent years. Summary of the Invention
[0005] In view of the insufficient research on the CaO-SiO2-B2O3 (CBS) microcrystalline glass system in the prior art, the present invention has developed a high thermal conductivity, high bending resistance Bi-based amorphous glass, CBS microcrystalline glass and alumina ceramic composite low-temperature co-fired ceramic (LTCC) material. By using alumina (Al2O3) as the ceramic phase, Bi2O3-ZnO-Al2O3-B2O3 (BZAB) and CaO-B2O3-SiO2 (CBS) as the glass phase, and by changing the ratio of the two glasses in the glass / ceramic composite material to improve the sintering condition, dielectric properties and mechanical properties of the composite material, the various properties of the prepared high thermal conductivity, high bending resistance Bi-based amorphous glass + CBS microcrystalline glass / alumina ceramic composite low-temperature co-fired ceramic (LTCC) material are comprehensively improved.
[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solution: the present invention provides a Bi-based amorphous glass, CBS microcrystalline glass and alumina ceramic composite low-temperature co-fired ceramic material, including the following components: the mass fraction of Bi-based amorphous glass is 25%-40%, the mass fraction of CBS microcrystalline glass is 5%-20%; the mass fraction of alumina is 55%.
[0007] Specifically, in some embodiments, the CBS glass-ceramics of the present invention comprises: 35 wt%-45 wt% CaCO3, 20 wt%-30 wt% H3BO3, and 25 wt%-35 wt% SiO2.
[0008] Preferably, the CBS glass-ceramics also contains some trace dopants selected from one or more of P2O5, Na2O, MgO, and SrO.
[0009] Specifically, the Bi-based amorphous glass comprises 62% Bi2O3, 6% ZnO, 6% Al2O3, and 26% B2O3.
[0010] Another object of the present invention is to provide a method for preparing a glass / ceramic composite low-dielectric-loss LTCC material, the method comprising the following steps:
[0011] S1. Preparation of Bi-based amorphous glass powder: The mixed powder of Bi2O3, ZnO, Al2O3, B2O3 was melted at 1400-1500 ℃ to obtain a glass liquid, which was then ground into a glass powder after cooling and forming;
[0012] S2 preparation of CBS glass-ceramics powder: CaCO3, H3BO3, SiO2 mixed powder by 1400-1500 ℃ melt glass liquid, after cooling and grinding into glass powder;
[0013] S3. Mix Bi-based amorphous glass powder, CBS micro-ceramic glass powder and alumina, mix them by alcohol ball milling, and dry them to obtain a low-temperature co-fired ceramic material composed of Bi-based amorphous glass, CBS micro-ceramic glass and alumina ceramic with high thermal conductivity and high bending resistance.
[0014] Specifically, in some embodiments, step S1 of the present invention is to take samples in a ratio of 62% Bi2O3, 6% ZnO, 6% Al2O3, and 26% B2O3, put them into a planetary ball mill, use a nylon ball mill jar with built-in zirconium balls, and use anhydrous ethanol as the ball milling medium to fully mix them. After the mixed slurry is dried, the powder is placed in a platinum crucible: the crucible with the built-in powder is placed in a high-temperature furnace and kept warm at 1400°C for 4 hours to obtain a high-temperature molten glass liquid; the obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven size, and the obtained glass blocks are crushed to obtain glass powder, thereby obtaining Bi-based amorphous glass powder.
[0015] Specifically, in some embodiments, in step S2 of the present invention, samples are taken in a ratio of 35wt%-45wt% CaCO3, 20wt%-30wt% H3BO3, and 25wt%-35wt% SiO2, placed in a planetary ball mill, and a nylon ball mill jar with built-in zirconium balls is used. Anhydrous ethanol is used as the ball milling medium for thorough mixing. After the mixed slurry is dried, the powder is placed in a platinum crucible: the crucible with the built-in powder is placed in a high-temperature furnace and kept warm at 1400°C for 4 hours to obtain a high-temperature molten glass liquid; the obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven size, and the obtained glass blocks are crushed to obtain glass powder, thereby obtaining CBS microcrystalline glass powder.
[0016] Specifically, in some embodiments, in step S3 of the present invention, the Bi-based amorphous glass obtained in step S2, the CBS microcrystalline glass powder obtained in step S3 and the alumina ceramic powder are mixed in a ratio of 25%-40% by mass of the Bi-based amorphous glass and 5%-20% by mass of the CBS microcrystalline glass; the alumina mass fraction is 55%, the anhydrous ethanol ball milling time is 6 hours, the rotation speed is 280r / min, and the mixed slurry is dried to obtain this Bi-based amorphous glass, CBS microcrystalline glass and alumina ceramic composite low-temperature co-fired ceramic material.
[0017] Another object of the present invention is to provide the application of the Bi-based amorphous glass, CBS microcrystalline glass and alumina ceramic composite low-temperature co-fired ceramic material in the preparation of microelectronic components. The Bi2O3-ZnO-Al2O3-B2O3 amorphous glass + CBS microcrystalline glass / alumina ceramic composite LTCC material can be sintered densely below 900°C, with a dielectric constant of 9.18-7.21 and a dielectric loss of 0.9×10 -3 -1.6×10-3 (1MHz).
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The present invention provides a high thermal conductivity, high bending resistance Bi-based amorphous glass, CBS micro-ceramic glass and alumina ceramic composite low temperature co-fired ceramic (LTCC) material and a preparation method thereof. By using alumina (Al2O3) as a ceramic phase, Bi2O3-ZnO-Al2O3-B2O3 (BZAB) and CaO-B2O3-SiO2 (CBS) as glass phases, the prepared high thermal conductivity, high bending resistance Bi-based amorphous glass, CBS micro-ceramic glass and alumina ceramic composite low temperature co-fired ceramic (LTCC) material can be fired at a temperature below 900°C when used to prepare microelectronic components. At the same time, the dielectric constant is 9.18-7.21, and the dielectric loss is 0.9×10 -3 -1.6×10 -3 (1MHz) Its mechanical properties include a flexural strength of 300±41MPa and a thermal conductivity of 4.25W / m·K.
[0020] Figures in the specification
[0021] Figure 1 Shown is a schematic diagram of the preparation process flow of the LTCC material in the present invention.
[0022] Figure 2 Shown is the microscopic morphology of the LTCC composite material prepared in the present invention.
[0023] Figure 3 Shown are the XRD patterns and EDS element line scan patterns of the LTCC composite material prepared in the present invention co-fired with Ag. DETAILED DESCRIPTION
[0024] The present invention will be further described below in conjunction with specific examples and accompanying drawings. It will be understood by those skilled in the art that the following examples are only used to further illustrate the present invention and are not to be construed as limiting the scope of the present invention. In the following examples, all raw materials are known commercially available products.
[0025] This embodiment provides a high thermal conductivity, high bending strength Bi-based amorphous glass, CBS glass-ceramics and alumina ceramic composite low-temperature co-fired ceramic (LTCC) material. The composite material comprises, by mass:
[0026] The mass fraction of Bi-based amorphous glass is 25%-40%;
[0027] The mass fraction of CBS glass-ceramics is 5%-20%;
[0028] The mass fraction of aluminum oxide is 55%.
[0029] The total amount of the Bi-based amorphous glass, CBS microcrystalline glass and aluminum oxide added is 100 parts by mass.
[0030] In this embodiment, the alumina is used as the ceramic phase, and the Bi-based amorphous glass and CBS glass-ceramics are used as the glass phase. First, the Bi-based amorphous glass obtained above is used with the Al2O3 ceramic phase to prepare a glass / ceramic LTCC composite material. Next, the Bi-based amorphous glass is partially replaced by the CBS glass-ceramics obtained above, thereby preparing a series of Bi-based amorphous glass + CBS glass-ceramics / alumina ceramic composite low-temperature co-fired ceramic (LTCC) materials. Mix the materials according to the above-mentioned component types to prepare the required glass / ceramic composite material, put it into a nylon ball mill, add zirconium balls and alcohol to wet mix, and ball mill for 6 hours. Then, dry it and sieve it to obtain the required composite material.
[0031] In the Bi-based amorphous glass and Al2O3 ceramic phase, glass / ceramic LTCC composite material prepared in the first step, the Bi-based amorphous glass plays a role of liquid phase sintering in the composite material as the sintering temperature increases, and forms a liquid phase to wrap the Al2O3 ceramic phase during the sintering process, thereby achieving sintering densification of the composite material. However, through SEM characterization of its microstructure, it was found that the liquid phase generated in the Bi-based amorphous glass and Al2O3 glass / ceramic LTCC composite material during the sintering process was insufficient and had poor fluidity, which could not effectively promote the sintering densification of the composite material. In addition, the dielectric properties of this composite material were poor due to the large proportion of glass phase, which was manifested as a high dielectric loss of 1.6×10 -3 To address the aforementioned issues with Bi-based amorphous glass and Al2O3 glass / ceramic LTCC composites, CBS glass-ceramics were introduced to partially replace the Bi-based amorphous glass. This resulted in a glass / Al2O3 ceramic phase LTCC composite material with a Bi-based amorphous glass + CBS glass-ceramics mixed glass component. Because this CBS glass-ceramics can spontaneously precipitate a calcium silicate crystal phase during the sintering process, it can achieve the goal of optimizing dielectric properties.
[0032] The glass / ceramic composite material obtained according to the above operation is dried and sieved (first through 60 mesh) to make the powder uniformly dispersed. Then, the dielectric properties are tested by dry pressing: a 5% PVA solution is added to the sieved composite powder for granulation. Next, a round disc-shaped green body with a diameter of 12mm and a thickness of about 1mm is formed by dry pressing through a mold. Then, it is placed in a muffle furnace for debinding and sintering. Test: The sintered ceramic sheet is silvered on both sides. Finally, the performance of the disc is tested by impedance analyzer 4291A. The dielectric constant is 9.18-7.21, and the dielectric loss is 0.9×10 -3 -1.6×10 -3 (1MHz).
[0033] refer to Figure 1 , provides a preparation method of Bi-based amorphous glass + CBS microcrystalline glass / alumina ceramic composite low-temperature co-fired ceramic (LTCC) material with high thermal conductivity and high bending resistance, including:
[0034] S1. Preparation of Bi-based amorphous glass powder;
[0035] S2. Preparation of CBS glass-ceramic powder:
[0036] S3. Mix Bi-based amorphous glass powder, CBS micro-ceramic glass powder and alumina, mix them by alcohol ball milling, and dry them to obtain a low-temperature co-fired ceramic material composed of Bi-based amorphous glass, CBS micro-ceramic glass and alumina ceramic with high thermal conductivity and high bending resistance.
[0037] Furthermore, the preparation of Bi-based amorphous glass powder includes: components including 62% Bi2O3, 6% ZnO, 6% Al2O3, and 26% B2O3, and the mixed powder of Bi2O3, ZnO, Al2O3, and B2O3 is melted at 1400-1500°C to obtain glass liquid, which is then cooled and formed and then ground into glass powder.
[0038] The CBS glass-ceramic powder is prepared as follows: the components include CaCO3: 35wt%-45wt%; H3BO3: 20wt%-30wt%; SiO2: 25wt%-35wt%
[0039] The mixed powder of CaCO3, H3BO3 and SiO2 is melted at 1400-1500℃ to obtain glass liquid, which is then ground into glass powder after cooling and forming.
[0040] It is understandable that the preparation process of Bi-based amorphous glass and CBS microcrystalline glass is well known in the art. The preparation method of some specific embodiments of the present application is: the ingredients are prepared according to the above-mentioned component contents, and then wet ball milled with alcohol, dried, and sieved to obtain a mixed powder; the mixed powder is melted into glass liquid at 1400-1500℃ for 24 hours, and then cooled by water quenching to form glass blocks, and then the glass blocks are broken into slurry by ball mill and dried and sieved to obtain glass powder.
[0041] The specific steps are as follows:
[0042] The preparation process parameters of Bi-based amorphous glass are as follows: first, the materials are weighed according to the proportion and placed in a platinum crucible. The glass liquid is melted at 1400℃-1500℃ for 2-4 hours. The water-quenched glass blocks are put into a ball mill and broken into slurry. Finally, the slurry is dried and sieved. The obtained glass powder is a uniform glass powder with a D50 of 3μm.
[0043] The preparation process parameters of CBS microcrystalline glass are as follows: first, the materials are weighed according to the proportion and placed in a platinum crucible. The glass liquid is melted at 1400℃-1500℃ for 2-4 hours. The water-quenched glass blocks are put into a ball mill and broken into slurry. Finally, they are dried and sieved. The obtained glass powder is a uniform glass powder with a D50 of 3μm.
[0044] The Bi-based amorphous glass, CBS glass-ceramics, and Al2O3 ceramic phase obtained above were weighed according to the specified component ratios. The materials were mixed according to the aforementioned proportions to prepare the desired glass / ceramic composite. The composite was then placed in a nylon ball mill, wet-mixed with zirconium balls and alcohol. The mill was milled at a speed of 280 rpm for 6 hours, with 11 turnovers every 30 minutes. The composite was then dried and sieved to obtain the desired composite material.
[0045] The obtained glass / ceramic composite material was dried and sieved (first through 60 mesh) to make the powder uniformly dispersed. Then, the dielectric properties were tested by dry pressing: a 5% PVA solution was added to the sieved composite powder for granulation. Then, a green disc with a diameter of 12mm and a thickness of about 1mm was formed by dry pressing through a mold. The green disc was then placed in a muffle furnace for debinding and sintering. Test: The sintered ceramic disc was silvered on both sides. Finally, the performance of the disc was tested by an impedance analyzer 4291A. The dielectric constant was 9.18-7.21, and the dielectric loss was 0.9×10 -3 -1.6×10 -3 (1MHz).
[0046] It is understandable that those skilled in the art can make substitutions or improvements based on the above preparation method without exceeding the conventional knowledge in the art, and various technical parameters can also be adjusted routinely within the knowledge.
[0047] Other embodiments of the present application disclose the use of the above-mentioned low-temperature co-fired ceramic / glass composite material in the preparation of microelectronic components. During the preparation, the sintering temperature of the low-temperature co-fired ceramic / glass composite material is 825-925°C.
[0048] In this embodiment, since the low-temperature co-fired ceramic / glass composite material of the present application has cheap raw materials, low production cost and simple preparation process, and the prepared material has excellent dielectric properties, it can be used in the manufacture of microwave devices such as low-temperature co-fired ceramic systems (LTCC), multilayer dielectric resonators, microwave antennas, filters, etc., and has great application value in industry.
[0049] Example 1 Preparation of high thermal conductivity, high bending strength Bi-based amorphous glass + CBS microcrystalline glass / alumina ceramic composite low temperature co-fired ceramic (LTCC) material
[0050] S1. First, prepare Bi-based amorphous glass: 62% Bi2O3, 6% ZnO, 6% Al2O3, and 26% B2O3; sample according to the established ratio, place in a planetary ball mill, use a nylon ball mill with built-in zirconium balls, and use anhydrous ethanol as the ball milling medium, mix thoroughly, dry the mixed slurry, and then place the powder in a platinum crucible: place the crucible with the built-in powder in a high-temperature furnace, keep it warm at 1400°C for 4 hours, and obtain high-temperature molten glass liquid.
[0051] S2. The obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven size. The obtained glass blocks are crushed to obtain glass powder, thereby obtaining Bi-based amorphous glass powder with a particle size D50 of 3-4 μm.
[0052] S3. Next, prepare CBS glass-ceramics: Sample 43.5wt% CaCO3; 24.5wt% H3BO3; 28.5wt% SiO2; 1.5wt% P2O5; 1.5wt% MgO; and 0.5wt% Na2O according to the established ratio, place them in a planetary ball mill, use a nylon ball mill with built-in zirconium balls, and use anhydrous ethanol as the ball milling medium. Thoroughly mix the mixed slurry, dry it, and then place the powder in a platinum crucible. Place the crucible containing the powder in a high-temperature furnace and keep it at 1400°C for 4 hours to obtain a high-temperature molten glass liquid.
[0053] S4. The obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven size. The obtained glass blocks are crushed to obtain glass powder, thereby obtaining CBS microcrystalline glass powder with a particle size D50 of 3-4 μm.
[0054] S5. The Bi-based amorphous glass, CBS microcrystalline glass powder and alumina ceramic powder obtained above are mixed according to the proportions in Table 1, ball-milled with anhydrous ethanol for 6 h at a rotation speed of 280 r / min, and the mixed slurry is dried to obtain this high thermal conductivity, high bending resistance Bi-based amorphous glass + CBS microcrystalline glass / alumina ceramic composite low-temperature co-fired ceramic (LTCC) material.
[0055] Table 1
[0056] Components Bi-based amorphous glass CBS glass-ceramic <![CDATA[Al2O3]]> Quality score 32.5% 12.5% 55%
[0057] A 5% PVA solution was added to the sieved composite powder for granulation. Next, a green disc with a diameter of 12 mm and a thickness of approximately 1 mm was formed through dry pressing in a mold. The green disc was then placed in a muffle furnace for debinding and sintering. During the debinding process, the temperature was raised to 500°C at 1°C / min and held for 5 hours. Next, the temperature was raised to 850°C at 5°C / min and held for 1 hour before sintering. Testing: The sintered ceramic discs were silvered on both sides. Finally, the performance of the discs was tested using an impedance analyzer 4291A, which showed a dielectric constant of 8.87 and a dielectric loss of 1.1×10 -3 (1MHz), flexural strength is 300±41MPa, thermal expansion coefficient is 6.36PPm / ℃, and thermal conductivity is 4.25W / m·K.
[0058] Example 2 Preparation of high thermal conductivity, high bending strength Bi-based amorphous glass + CBS microcrystalline glass / alumina ceramic composite low temperature co-fired ceramic (LTCC) material
[0059] S1. First, prepare Bi-based amorphous glass: 62% Bi2O3, 6% ZnO, 6% Al2O3, and 26% B2O3; sample according to the established ratio, place in a planetary ball mill, use a nylon ball mill with built-in zirconium balls, and use anhydrous ethanol as the ball milling medium, mix thoroughly, dry the mixed slurry, and then place the powder in a platinum crucible: place the crucible with the built-in powder in a high-temperature furnace, keep it warm at 1400°C for 4 hours, and obtain high-temperature molten glass liquid.
[0060] S2. The obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven size. The obtained glass blocks are crushed to obtain glass powder, thereby obtaining Bi-based amorphous glass powder with a particle size D50 of 3-4 μm.
[0061] S3. Next, prepare CBS glass-ceramics: Sample 43.5wt% CaCO3; 24.5wt% H3BO3; 28.5wt% SiO2; 1.5wt% P2O5; 1.5wt% MgO; and 0.5wt% Na2O according to the established ratio, place them in a planetary ball mill, use a nylon ball mill with built-in zirconium balls, and use anhydrous ethanol as the ball milling medium. Thoroughly mix the mixed slurry, dry it, and then place the powder in a platinum crucible. Place the crucible containing the powder in a high-temperature furnace and keep it at 1400°C for 4 hours to obtain a high-temperature molten glass liquid.
[0062] S4. The obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven size. The obtained glass blocks are crushed to obtain glass powder, thereby obtaining CBS microcrystalline glass powder with a particle size D50 of 3-4 μm.
[0063] S5. The Bi-based amorphous glass, CBS microcrystalline glass powder and alumina ceramic powder obtained above are mixed according to the proportions in Table 2, ball-milled with anhydrous ethanol for 6 h at a rotation speed of 280 r / min, and the mixed slurry is dried to obtain this high thermal conductivity and high bending resistance Bi-based amorphous glass + CBS microcrystalline glass / alumina ceramic composite low-temperature co-fired ceramic (LTCC) material.
[0064] Table 2
[0065] Components Bi-based amorphous glass CBS glass-ceramic <![CDATA[Al2O3]]> Quality score 40% 5% 55%
[0066] A 5% PVA solution was added to the sieved composite powder for granulation. Next, a green disc with a diameter of 12 mm and a thickness of approximately 1 mm was formed through dry pressing in a mold. The green disc was then placed in a muffle furnace for debinding and sintering. During the debinding process, the temperature was raised to 500°C at 1°C / min and held for 5 hours. Next, the temperature was raised to 850°C at 5°C / min and held for 1 hour before sintering. Testing: The sintered ceramic discs were silvered on both sides. Finally, the performance of the discs was tested using an impedance analyzer 4291A, which showed a dielectric constant of 8.13 and a dielectric loss of 1.5×10 -3 (1MHz).
[0067] Example 3 Preparation of high thermal conductivity, high bending strength Bi-based amorphous glass + CBS microcrystalline glass / alumina ceramic composite low temperature co-fired ceramic (LTCC) material
[0068] S1. First, prepare Bi-based amorphous glass: 62% Bi2O3, 6% ZnO, 6% Al2O3, and 26% B2O3; sample according to the established ratio, place in a planetary ball mill, use a nylon ball mill with built-in zirconium balls, and use anhydrous ethanol as the ball milling medium, mix thoroughly, dry the mixed slurry, and then place the powder in a platinum crucible: place the crucible with the built-in powder in a high-temperature furnace, keep it warm at 1400°C for 4 hours, and obtain high-temperature molten glass liquid.
[0069] S2. The obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven size. The obtained glass blocks are crushed to obtain glass powder, thereby obtaining Bi-based amorphous glass powder with a particle size D50 of 3-4 μm.
[0070] S3. Next, prepare CBS glass-ceramics: Sample 43.5wt% CaCO3; 24.5wt% H3BO3; 28.5wt% SiO2; 1.5wt% P2O5; 1.5wt% MgO; and 0.5wt% Na2O according to the established ratio, place them in a planetary ball mill, use a nylon ball mill with built-in zirconium balls, and use anhydrous ethanol as the ball milling medium. Thoroughly mix the mixed slurry, dry it, and then place the powder in a platinum crucible. Place the crucible containing the powder in a high-temperature furnace and keep it at 1400°C for 4 hours to obtain a high-temperature molten glass liquid.
[0071] S4. The obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven size. The obtained glass blocks are crushed to obtain glass powder, thereby obtaining CBS microcrystalline glass powder with a particle size D50 of 3-4 μm.
[0072] S5. The Bi-based amorphous glass, CBS microcrystalline glass powder and alumina ceramic powder obtained above are mixed according to the proportions in Table 3, ball-milled with anhydrous ethanol for 6 h at a rotation speed of 280 r / min, and the mixed slurry is dried to obtain this high thermal conductivity, high bending resistance Bi-based amorphous glass + CBS microcrystalline glass / alumina ceramic composite low-temperature co-fired ceramic (LTCC) material.
[0073] Table 3
[0074] Components Bi-based amorphous glass CBS glass-ceramic <![CDATA[Al2O3]]> Quality score 37.5% 7.5% 55%
[0075] A 5% PVA solution was added to the sieved composite powder for granulation. Next, a green disc with a diameter of 12 mm and a thickness of approximately 1 mm was formed through dry pressing using a mold. The green disc was then placed in a muffle furnace for debinding and sintering. During the debinding process, the temperature was raised to 500°C at 1°C / min and held for 5 hours. Next, the temperature was raised to 850°C at 5°C / min and held for 1 hour before sintering. Testing: The sintered ceramic discs were silvered on both sides. Finally, the performance of the discs was tested using an impedance analyzer 4291A, which showed a dielectric constant of 8.61 and a dielectric loss of 1.3×10 -3 (1MHz).
[0076] Example 4 Preparation of high thermal conductivity, high bending strength Bi-based amorphous glass + CBS microcrystalline glass / alumina ceramic composite low temperature co-fired ceramic (LTCC) material
[0077] S1. First, prepare Bi-based amorphous glass: 62% Bi2O3, 6% ZnO, 6% Al2O3, and 26% B2O3; sample according to the established ratio, place in a planetary ball mill, use a nylon ball mill with built-in zirconium balls, and use anhydrous ethanol as the ball milling medium, mix thoroughly, dry the mixed slurry, and then place the powder in a platinum crucible: place the crucible with the built-in powder in a high-temperature furnace, keep it warm at 1400°C for 4 hours, and obtain high-temperature molten glass liquid.
[0078] S2. The obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven size. The obtained glass blocks are crushed to obtain glass powder, thereby obtaining Bi-based amorphous glass powder with a particle size D50 of 3-4 μm.
[0079] S3. Next, prepare CBS glass-ceramics: Sample 43.5wt% CaCO3; 24.5wt% H3BO3; 28.5wt% SiO2; 1.5wt% P2O5; 1.5wt% MgO; and 0.5wt% Na2O according to the established ratio, place them in a planetary ball mill, use a nylon ball mill with built-in zirconium balls, and use anhydrous ethanol as the ball milling medium. Thoroughly mix the mixed slurry, dry it, and then place the powder in a platinum crucible. Place the crucible containing the powder in a high-temperature furnace and keep it at 1400°C for 4 hours to obtain a high-temperature molten glass liquid.
[0080] S4. The obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven size. The obtained glass blocks are crushed to obtain glass powder, thereby obtaining CBS microcrystalline glass powder with a particle size D50 of 3-4 μm.
[0081] S5. The Bi-based amorphous glass, CBS microcrystalline glass powder and alumina ceramic powder obtained above are mixed according to the proportions in Table 4, ball-milled with anhydrous ethanol for 6 h at a rotation speed of 280 r / min, and the mixed slurry is dried to obtain this high thermal conductivity and high bending resistance Bi-based amorphous glass + CBS microcrystalline glass / alumina ceramic composite low-temperature co-fired ceramic (LTCC) material.
[0082] Table 4
[0083] Components Bi-based amorphous glass CBS glass-ceramic <![CDATA[Al2O3]]> Quality score 35% 10% 55%
[0084] A 5% PVA solution was added to the sieved composite powder for granulation. Next, the green discs were dry-pressed through a mold into discs approximately 12 mm in diameter and 1 mm thick. The discs were then placed in a muffle furnace for debinding and sintering. During the debinding process, the temperature was raised to 500°C at a rate of 1°C / min and held for 5 hours. Next, the temperature was raised to 850°C at a rate of 5°C / min and held for 1 hour before sintering. Testing: The sintered discs were silver-coated on both sides. Finally, impedance analysis using a 4291A impedance analyzer revealed a dielectric constant of 9.09 and a dielectric loss of 1.2 × 10⁻³ (1 MHz).
[0085] Example 5 Preparation of high thermal conductivity, high bending strength Bi-based amorphous glass + CBS microcrystalline glass / alumina ceramic composite low temperature co-fired ceramic (LTCC) material
[0086] S1. First, prepare Bi-based amorphous glass: 62% Bi2O3, 6% ZnO, 6% Al2O3, and 26% B2O3; sample according to the established ratio, place in a planetary ball mill, use a nylon ball mill with built-in zirconium balls, and use anhydrous ethanol as the ball milling medium, mix thoroughly, dry the mixed slurry, and then place the powder in a platinum crucible: place the crucible with the built-in powder in a high-temperature furnace, keep it warm at 1400°C for 4 hours, and obtain high-temperature molten glass liquid.
[0087] S2. The obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven size. The obtained glass blocks are crushed to obtain glass powder, thereby obtaining Bi-based amorphous glass powder with a particle size D50 of 3-4 μm.
[0088] S3. Next, prepare CBS glass-ceramics: Sample 43.5wt% CaCO3; 24.5wt% H3BO3; 28.5wt% SiO2; 1.5wt% P2O5; 1.5wt% MgO; and 0.5wt% Na2O according to the established ratio, place them in a planetary ball mill, use a nylon ball mill with built-in zirconium balls, and use anhydrous ethanol as the ball milling medium, and mix them thoroughly. After drying the mixed slurry, place the powder in a platinum crucible: place the crucible containing the powder in a high-temperature furnace, and keep it at 1400°C for 4 hours to obtain high-temperature molten glass liquid.
[0089] S4. The obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven size. The obtained glass blocks are crushed to obtain glass powder, thereby obtaining CBS microcrystalline glass powder with a particle size D50 of 3-4 μm.
[0090] S5. The Bi-based amorphous glass, CBS microcrystalline glass powder and alumina ceramic powder obtained above are mixed according to the proportions in Table 5, ball-milled with anhydrous ethanol for 6 h at a rotation speed of 280 r / min, and the mixed slurry is dried to obtain this high thermal conductivity and high bending resistance Bi-based amorphous glass + CBS microcrystalline glass / alumina ceramic composite low-temperature co-fired ceramic (LTCC) material.
[0091] Table 5
[0092] Components Bi-based amorphous glass CBS glass-ceramic <![CDATA[Al2O3]]> Quality score 30% 15% 55%
[0093] A 5% PVA solution was added to the sieved composite powder for granulation. Next, the green discs were dry-pressed through a mold into discs approximately 12 mm in diameter and 1 mm thick. The discs were then placed in a muffle furnace for debinding and sintering. During the debinding process, the temperature was raised to 500°C at 1°C / min and held for 5 hours. Next, the temperature was raised to 850°C at 5°C / min and held for 1 hour before sintering. Testing: The sintered discs were silver-coated on both sides. Finally, impedance analysis using a 4291A impedance analyzer revealed a dielectric constant of 9.16 and a dielectric loss of 1.0 × 10⁻³ (1 MHz).
[0094] Figure 2 This is a SEM microscopic morphology of the optimal component in the glass / ceramic composite material in Example 1 of the present invention at a sintering temperature of 850°C. It can be found that the secondary composite material system can obtain an internal structure with a high degree of densification at a lower sintering temperature.
[0095] Figure 3 The XRD and EDS line scans of the glass / ceramic composite material of Example 1 of the present invention after co-firing with Ag show that it has good compatibility with Ag at a sintering temperature of 850°C, creating conditions for subsequent actual production and use.
[0096] The present invention provides a method for preparing a high-thermal-conductivity, high-bending-resistance Bi-based amorphous glass + CBS glass-ceramic / alumina ceramic composite low-temperature co-fired ceramic (LTCC) material. During the sintering process, the Bi-based amorphous glass acts as a liquid-phase sintering agent in the composite material as the sintering temperature increases. During the sintering process, a liquid phase encapsulates the Al2O3 ceramic phase, thereby achieving sintering densification of the composite material. CBS glass-ceramic is introduced to partially replace the Bi-based amorphous glass, thereby preparing a Bi-based amorphous glass + CBS glass-ceramic mixed glass component, a glass / Al2O3 ceramic phase LTCC composite material. The CBS glass-ceramic can also spontaneously precipitate a calcium silicate crystal phase during the sintering process, thereby achieving the purpose of optimizing dielectric properties. The prepared LTCC glass / ceramic composite material can be sintered below 950°C and has excellent dielectric properties: a dielectric constant of 9.18-7.21 and a dielectric loss of 0.9×10 -3 -1.6×10 -3 (1MHz), high flexural strength of 300±41MPa, and high thermal conductivity make this material have excellent thermal conductivity of 4.25W / m·K.
[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low temperature co-fired ceramic material composed of Bi-based amorphous glass, CBS glass-ceramics and alumina ceramics, characterized in that: The invention comprises the following components: the mass fraction of Bi-based amorphous glass is 25%-40%, the mass fraction of CBS microcrystalline glass is 5%-20%; and the mass fraction of aluminum oxide is 55%.
2. The ceramic material according to claim 1, characterized in that The CBS glass-ceramics components include: 35wt%-45wt% CaCO3, 20wt%-30wt% H3BO3, and 25wt%-35wt% SiO2.
3. The ceramic material according to claim 2, characterized in that The CBS glass-ceramics also contains some trace dopants, selected from one or more of P2O5, Na2O, MgO, and SrO.
4. The ceramic material according to claim 1, characterized in that The Bi-based amorphous glass comprises: 62% Bi2O3, 6% ZnO, 6% Al2O3, and 26% B2O3.
5. A method for preparing a glass / ceramic composite low dielectric and low loss LTCC material, characterized in that: The method comprises the following steps: S1. Preparation of Bi-based amorphous glass powder: The mixed powder of Bi2O3, ZnO, Al2O3 and B2O3 is melted at 1400-1500°C to obtain a glass liquid, which is then ground into a glass powder after being cooled and formed; S2. Preparation of CBS glass-ceramics powder: The mixed powder of CaCO3, H3BO3 and SiO2 is melted at 1400-1500°C to obtain a glass liquid, which is then ground into glass powder after being cooled and formed; S3. Mix Bi-based amorphous glass powder, CBS microcrystalline glass powder and alumina, mix by alcohol ball milling and dry, and obtain a low-temperature co-fired ceramic material of Bi-based amorphous glass, CBS microcrystalline glass and alumina ceramic with high thermal conductivity and high bending resistance.
6. The preparation method according to claim 5, characterized in that: The step S1. takes samples according to the proportion of 62% Bi2O3, 6% ZnO, 6% Al2O3, and 26% B2O3, puts them into a planetary ball mill, uses a nylon ball mill with built-in zirconium balls, uses anhydrous ethanol as a ball milling medium, mixes them thoroughly, dries the mixed slurry, and then puts the powder into a platinum crucible: puts the crucible with the built-in powder into a high-temperature furnace, keeps it warm at 1400°C for 4 hours, and obtains high-temperature molten glass liquid; pours the obtained glass solution into deionized water for cooling and quenching to obtain glass blocks of uneven size, and crushes the obtained glass blocks to obtain glass powder, thereby obtaining Bi-based amorphous glass powder.
7. The preparation method according to claim 5, characterized in that: In the step S2, samples are taken according to the ratio of 35wt%-45wt% CaCO3, 20wt%-30wt% H3BO3, and 25wt%-35wt% SiO2, and are put into a planetary ball mill. A nylon ball mill is used with zirconium balls built in, and anhydrous ethanol is used as a ball milling medium for thorough mixing. After the mixed slurry is dried, the powder is then put into a platinum crucible: the crucible with the built-in powder is put into a high-temperature furnace and kept warm at 1400°C for 4 hours to obtain a high-temperature molten glass liquid; the obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven size, and the obtained glass blocks are crushed to obtain glass powder, thereby obtaining CBS microcrystalline glass powder.
8. The preparation method according to claim 5, characterized in that: In the step S3, the Bi-based amorphous glass obtained in the step S2, the CBS microcrystalline glass powder obtained in the step S3 and the alumina ceramic powder are mixed in a ratio of 25%-40% by mass of the Bi-based amorphous glass and 5%-20% by mass of the CBS microcrystalline glass; the alumina mass fraction is 55%, the anhydrous ethanol ball milling time is 6 hours, the rotation speed is 280r / min, and the mixed slurry is dried to obtain the Bi-based amorphous glass, CBS microcrystalline glass and alumina ceramic composite low-temperature co-fired ceramic material.
9. Use of the Bi-based amorphous glass, CBS glass-ceramics and alumina ceramic composite low-temperature co-fired ceramic material according to any one of claims 1 to 5 in the preparation of microelectronic components, wherein the sintering temperature of the ceramic material is below 900°C during the preparation.
Citation Information
Patent Citations
Low temperature sintered glass-ceramic composite insulating material and preparation method thereof
CN104844002A
Pre-nucleation glass powder for automobile glass ink and preparation method of pre-nucleation glass powder
CN108083651A
Bismuth oxide-niobium oxide based LTCC substrate material and preparation method thereof
CN110156455A
Heat-conducting low-temperature co-fired ceramic material and preparation method thereof
CN110683837A
Low dielectric constant and high temperature stability LTCC material and preparation method thereof
CN115594405A